From Clinical Clues to Final Diagnosis: The Return of Detective Work to Clinical Medicine in Cardiac Amyloidosis - Sabbour, Hani; Hasan, Khwaja Yousuf; Al Badarin, Firas; Alibazoglu, Haluk; Rivard, Andrew L.; Romany, Ingy; Perlini, Stefano (Frontiers in Cardiovascular Medicine, 2021)
Cardiac amyloidosis is frequently misdiagnosed, denying patients the opportunity for timely and appropriate management of the disease. The purpose of this review and case studies is to raise awareness of the diagnostic “red flags” associated with cardiac amyloidosis and the currently available non-invasive strategies for diagnosis. The review focuses on the identification of one of the two main types of cardiac amyloidosis, transthyretin amyloid cardiomyopathy, and non-invasive tools to distinguish this from light-chain amyloidosis. A diagnostic algorithm centered around the use of non-invasive imaging and laboratory analysis is presented. The algorithm generates four differential diagnoses for patients presenting with signs and symptoms consistent with cardiac amyloidosis. Case examples are presented, representing the four potential outcomes of diagnosis using the algorithm. The review provides a guide on how to recognize the often-overlooked presentations of this disease in clinical practice. Non-invasive imaging techniques and diagnostic tools that do not require the involvement of a specialty center have allowed for the improved diagnosis of cardiac amyloidosis. Timely diagnosis of this life-threatening disease is essential for optimal management and it is imperative that clinicians have a high index of suspicion for patients presenting with “red flag” symptoms.